PEST PROBLEMS OF COCONUT HYBRID PRODUCTION IN INDONESIA WITH SPECIAL REFERENCE TO SCDP - Dante R.A. Benigno, PhD.; Ir. Soetardjo Soewarno (International Coconut Community, 1985)
SCDP is a World Bank and Government of Indonesia fundect project managed by the Directorate General of Estates of the Ministry of Agriculture. This project is responsbile for the planting of coconut hybrids as well as local talls, but mostly hybrids. Since 1981 to date, some 22,000 ha have already been planted to hybrids in 70 coconut working centers (CWC) widely scattered in 6 provinces such as Aceh, Lampung, South Sulawesi, Central Sulawesi, North Sulawesi, and Maluku (Fig.1).